Why Do We Need New Drug Classes for HIV Treatment and Prevention? - A. Waheed, Abdul; Tachedjian, Gilda (Current Topics in Medicinal Chemistry, 2016)
The biomedical intervention that has had a major impact on the natural history of HIV and on the global HIV epidemic is antiretroviral therapy (ART). However, the emergence of drug-resistant HIV, an inevitable consequence of increasing use of antiretroviral drugs, poses a major threat to ART success. At the turn of this century, access to life-saving ART was accelerated in low and middle-income countries with the Millennium Development Goal of 15 million individuals receiving ART by 2015 expected to be achieved. However, ART access needs to continue to expand to help bring HIV under control by 2030. The standard of care for people living with HIV in resource- limited settings differs dramatically compared to high-income countries, and not unexpectedly, ART rollout in these settings has resulted in an increase in acquired and transmitted drug resistance. Also of concern, the same drug classes used for ART have been approved or are being progressed for HIV prevention and drug resistance could mitigate their effectiveness for treatment and prevention. In the absence of an effective HIV vaccine and cure, it is imperative that the antiretroviral drug pipeline contains new classes of HIV inhibitors that are active against circulating drug-resistant strains. Studies to advance our fundamental understanding of HIV replication needs to continue, including the interplay between virus and host cell factors, to identify and characterize new drug targets for chemotherapeutic intervention.
Keywords: Drug resistance